An investigation of regional cerebral blood flow and tissue structure changes after acute administration of antipsychotics in healthy male volunteers. Issue 1 (23rd October 2017) - Hawkins, Peter C.T.; Wood, Tobias C.; Vernon, Anthony C.; Bertolino, Alessandro; Sambataro, Fabio; Dukart, Juergen; Merlo‐Pich, Emilio; Risterucci, Celine; Silber‐Baumann, Hanna; Walsh, Eamonn; Mazibuko, Ndabezinhle; Zelaya, Fernando O.; et al.
Abstract: Chronic administration of antipsychotic drugs has been linked to structural brain changes observed in patients with schizophrenia. Recent MRI studies have shown rapid changes in regional brain volume following just a single dose of these drugs. However, it is not clear if these changes represent real volume changes or are artefacts ("apparent" volume changes) due to drug‐induced physiological changes, such as increased cerebral blood flow (CBF). To address this, we examined the effects of a single, clinical dose of three commonly prescribed antipsychotics on quantitative measures of T1 and regional blood flow of the healthy human brain. Males ( n  = 42) were randomly assigned to one of two parallel groups in a double‐blind, placebo‐controlled, randomized, three‐period cross‐over study design. One group received a single oral dose of either 0.5 or 2 mg of risperidone or placebo during each visit. The other received olanzapine (7.5 mg), haloperidol (3 mg), or placebo. MR measures of quantitative T1, CBF, and T1‐weighted images were acquired at the estimated peak plasma concentration of the drug. All three drugs caused localized increases in striatal blood flow, although drug and region specific effects were also apparent. In contrast, all assessments of T1 and brain volume remained stable across sessions, even in those areas experiencing large changes in CBF. This illustrates that a single clinically relevant oral dose of an antipsychotic has no detectable acute effect on T1 in healthy volunteers. We further provide a methodology for applying quantitative imaging methods to assess the acute effects of other compounds on structural MRI metrics. Hum Brain Mapp 39:319–331, 2018 . ©2017 Wiley Periodicals, Inc.